MS-Computer Science Program Review 2016 (2016)
The Computer Science (CS) program at CSUCI provides strong undergraduate programs in both Computer Science and Information Technology, and a graduate program in Computer Science. We offer three minors that serve as specializations in Robotics, Game Design, and CyberSecurity. Our graduates are employed at a high rate in the "101 Technology Corridor" (latest study of alumni show that over 60% of Computer Science students are working within 3 months of graduation, but anecdotally we are certain that the figure is much higher). Our Master's degree program has also produced graduates who have done well in getting employment after graduation in industry, banking or research and development units.The paradigm of a CS faculty is a teacher-scholar, which means that we stress excellence both in teaching and research. Our faculty writes papers, presents at conferences, and applies for - and is awarded - grants. We have no trouble attracting students, and indeed, the CS department is growing every year. We have a strong relationship with the local community, especially the Navy, and we engage in interdisciplinary work with other programs on campus, notably Mathematics, ESRM (Environmental Science), and Biology.CS is a busy department. We are currently shouldering the weight of introducing Engineering to campus, we are collaborating with ESRM in drones, robots, and UAVs, we provide expertise in Cyber-Security, Algorithms, Social Media, and other areas. We are helping the university fundraise with the local community, we do outreach to the local industry, and we run clubs that compete at regional programming contests. We are enthusiastic about our work, but it is undeniable that we are stretched pretty thin. In particular, we absolutely need a dedicated admin staff (currently we are sharing one among 4 programs), a dedicated IT Lab person (we have brand new labs, but no staff), and funding for release time to continue developing the program.This is the second time in its short history that CS has undertaken a self-study. The chair of CS is new (joined CI in 2014), and during the time when the self-study was conducted (academic year 2015-16), the only other senior (tenured) faculty was on a half-year sabbatical, and the only administrative assistant was on maternity leave. Thus the chair ended up preparing the self-study during the summer 2016, at the time when the other faculty are not officially on campus (and catch up on much needed research time).